Impacts caused by COVID-19 on the Brazilian Education sector: An Application of Exploratory Factorial Analysis (Research, Society and Development, 2020)
The year 2020 was marked by the beginning of a pandemic caused by the new coronavirus (Covid-19). This virus of easy and rapid contagion has impacted several sectors around the world, and like many countries Brazil seeks to minimize such impacts. Due to the ease of contamination, restrictive measures had to be adopted, such as social distancing, causing the closure of industries, businesses, universities, schools, among others, always seeking to reduce contact between individuals. The educational sector was severely affected, with the extremely necessary implementation of measures to allow the school year continuity. This work aims to measure the impacts caused by COVID-19 on the educational field, through factorial analysis. Data was collected via a virtual questionnaire, which made it possible to analyze the effects of this scenario on the lives of education professionals. The results were satisfactory, showing factors that influence directly on the performance of professionals during this challenging period.